2019
DOI: 10.1002/bit.27173
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable zinc oxide composite scaffolds promote osteochondral differentiation of mesenchymal stem cells

Abstract: Osteoarthritis (OA) involves the degeneration of articular cartilage and subchondral bone. The capacity of articular cartilage to repair and regenerate is limited. A biodegradable, fibrous scaffold containing zinc oxide (ZnO) was fabricated and evaluated for osteochondral tissue engineering applications. ZnO has shown promise for a variety of biomedical applications but has had limited use in tissue engineering. Composite scaffolds consisted of ZnO nanoparticles embedded in slow degrading, polycaprolactone to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 74 publications
(107 reference statements)
2
42
0
1
Order By: Relevance
“…As mentioned above, the concentration of n‐ZnO did not show a significant effect on the osteoblast cell viability. Similar results have been presented by Khader and Arinzeh when studying human mesequimal cell proliferation in policaprolactone/ZnO fibrous mats 54 . However, several reports based on ZnO hybrid fibrous materials have presented a decrease on cell viability as ZnO concentration increases 13,55 .…”
Section: Discussionsupporting
confidence: 86%
“…As mentioned above, the concentration of n‐ZnO did not show a significant effect on the osteoblast cell viability. Similar results have been presented by Khader and Arinzeh when studying human mesequimal cell proliferation in policaprolactone/ZnO fibrous mats 54 . However, several reports based on ZnO hybrid fibrous materials have presented a decrease on cell viability as ZnO concentration increases 13,55 .…”
Section: Discussionsupporting
confidence: 86%
“…Safety is a second issue hindering treatment with hESC-MSCs, due to concerns about unwanted, unexpected, or uncontrolled differentiation of hESC-MSCs after transplantation [29]. Options to address this issue that have been introduced in numerous disease models include the use of bio-degradable [30] or biomimetic [31] scaffold-encapsulated MSCs, or of membrane-bound biological nanoparticles (exosomes) secreted by MSCs [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, ZnO-NPs can promote cartilage formation at lower concentrations. Khader et al 25 prepared ZnO/ PCL scaffolds with a concentration gradient of 1-10 wt% ZnO-NPs with an electrospinning technique. They found that under concentrations of 1-2.5wt%, the expression of cartilage markers such as SOX-9 and collagen type II were significantly increased in MSCs.…”
Section: Dovepressmentioning
confidence: 99%
“…In fact, studies have confirmed that implants of various materials, like metals and polymers decorated with ZnO-NPs via doping or coating, show better antibacterial and osteogenic abilities. 25,26 To our knowledge, this is the first article focused on summarizing the recent progresses of ZnO-NPs in orthopedic applications. The first part is a brief review on the green preparation methods.…”
Section: Introductionmentioning
confidence: 99%